Synthesis of Boiler Controllers of the Automatic Power Control System of Power Units - G. T. Kulakov; K. I. Artsiomenka (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The article concerns the problem of structure-and-parametric optimization of a cascade automatic control system (CACS) by an example of a boiler power controller and a fuel controller. This CACS, which is a part of automatic control systems for power units, consists of two loops, viz. of an inner loop (which purpose is stabilization of the system) and an outer loop (designed for the adjustment) and, also, of two controller, viz. an outer controller (which is a basic one) provided for stabilization of the output value of the object (in our case, of the actual power unit capacity) and of an inner controller (which is an auxiliary one) provided to regulate fuel consumption. The internal controller builds up the control action with the aid of the boiler load controller of the power unit. As compared to single-loop automatic control systems, the cascade  system provides better quality of transient control due to the higher performance of the internal loop of the system. This advantage is especially noticeable when compensating for disturbances that come through the channel of regulating impact. The article presents two methods of setting, viz. the fuel controller and the boiler power controller. The application of these methods can improve the quality of power control and reduce fuel consumption in transient modes in comparison with the setting of these controllers of a typical power unit automatic power control system. The results of computer simulation of transient processes in CACS for input step surge and internal perturbation confirm the advantages of the methods are presented in this article.